Derepression of transposable elements in the mouse prefrontal cortex disrupts social behavior - R. Kijoon Kim; Corinne Smith; Natalie L. Truby; Shelbey R. Strandberg; Jessica L. Bell; Nic Carwile; Gabriella M. Silva; Rachael L. Neve; Theingi Aung; Xiaohong Cui; Peter J. Hamilton (Proceedings of the National Academy of Sciences, 2025)
The neurobiological origins of social behaviors are poorly understood. Previous studies have linked the function of a single Krüppel-associated box zinc finger protein (KZFP), ZFP189, in the mouse prefrontal cortex (PFC), with the regulation of transposable elements (TEs), immune genes, and social behaviors. Here, we expand the scope of inquiry to explore the relationship between collective PFC KZFP function and social behaviors by altering the function of the cognate KZFP interacting protein TRIM28 within the PFC of male and female mice. We reprogrammed natural TRIM28 WT by replacing the endogenous, transcriptionally repressive domain with a synthetic, enhanced transcriptional activation domain VP64-p65-Rta (TRIM28 VPR ) or by excising the transcriptional regulatory domain (TRIM28 NFD ). Upon intra-PFC viral-mediated delivery of TRIM28 variants, we observed that inversion of TRIM28 transcriptional control via HSV-TRIM28 VPR selectively produced deficits in social behaviors, without affecting nonsocial behaviors. RNA sequencing of manipulated PFC revealed that HSV-TRIM28 VPR drove transcriptional escape of all classes of TEs, particularly those located within intronic and enhancer regions proximal to downregulated immune genes. HSV-TRIM28 VPR -mediated social deficits were reversible by intra-PFC repletion of interferon cytokines. These data point to PFC KZFP–TRIM28 interactions as necessary to stabilize genomic TEs to enable cis -regulation of key immune gene expression, which enhances organismal capacity for complex, prosocial behaviors.